(untitled) (Sustainability in Debate, 2015)
Currently, agriculture is one of the most discussed topics in the theoretical field of sustainability. Debates regarding this issue are increasingly recurrent and put in question the model adopted from the post-war, the so-called green revolution. In the state of Rio Grande do Norte, the agricultural potential lies mainly in irrigated horticulture, where stands the agropolo Acu-Mossoró as one of the greatest watermelon producing regions of Brazil. The cultivation of watermelon, once dominated by large agricultural companies, is currently developed by agroecosystems whose management is characterized by family participation, including small farmers of rural settlements created by Incra. Aiming to assess the sustainability of this type of cultivation, was used the MESMIS methodology in the in São Romão settlement in Mossoró-RN, which is primarily engaged in the cultivation of irrigated melon. Seven critical points were determined and selected twenty-three indicators that directly affect the sustainability of the researched area.